Phytochemical screening of selected plants and their allelopathic effect in germination of bean and radish seeds - Gautam Bahadur Khadka; Sameer Neupane; Santosh Phunyal (Fundamental and Applied Agriculture, 2023)
BACKGROUND: The study of ethno-botanical is important in different sectors like medical and agriculture so the discovery, exploration and documentation of such plants is necessary. This research assessed the phytochemicals present in the selected plants and studied their allelopathic effect on germination, radicle length, and plumule length of bean and radish seeds.